Beyond Competencies: Associations between Personality and School Grades Are Largely Independent of Subject-Specific and General Cognitive Competencies - Roemer, Lena; Lechner, Clemens M.; Rammstedt, Beatrice (Journal of intelligence, 2022)
The Big Five personality traits are established predictors of school grades. However, the mechanisms underlying these associations are not yet well understood. Effects of personality on grades might arise because behavioral tendencies facilitate learning and increase subject-specific competencies. Alternatively, personality effects on grades might be independent of cognitive competencies and reflect otherwise valued behaviors or teachers’ grading practices. In the current study, we drew on large-scale data of 7th and 9th graders in Germany to explore the extent to which personality predicted grades even after accounting for competencies. Controlling for competencies and other key covariates, we cross-sectionally and longitudinally examined personality–grade associations across different school subjects, grade levels, and school types. Results indicate that the predictive power of personality is largely independent of subject-specific and general cognitive competencies. The largest effects emerged for conscientiousness. For openness, associations with grades partly overlapped with competencies, suggesting that openness may operate by fostering competencies. Overall, our results suggest that the associations between personality and grades unfold mostly independently of course mastery. This finding underlines the socioemotional value of personality in the classroom and encourages a more fine-grained view of the interplay between personality, competencies, classroom behavior, and grades.